CPC-098 Osteoporosis After Lung Transplant. (12th March 2013) - Ging, P; Lawrie, I; Winward, S; Egan, JJ; Meegan, C
Abstract : Background: Osteoporosis after a lung transplant is common, with reported vertebral fracture rates of up to 30% [1]. Bisphosphonates, and calcium and vitamin D supplements may be less effective in patients who remain on steroid treatment [2]. Corticosteroids are more detrimental to spinal bone mineral density than to the hip [2]; however risk prediction systems use hip T-scores to predict risk and make treatment recommendations [3, 4]. We reviewed the prophylaxis of osteoporosis in a cohort of patients at the time of listing and up to 6 years post-transplant. Purpose: We wished to identify: any potential for improvement in prescribing risk factors for clinically significant lumbar fractures the utility of currently available osteoporosis risk algorithms in this cohort. Materials and Methods: We conducted a retrospective chart review (n = 27). Patients' risk of fracture at the time of listing for transplant was calculated using three different methods including WHO charts and American College of Rheumatology algorithm for steroid-treated patients. We attempted to create a model to predict fracture in transplant recipients using known risk factors. Results: At time of listing, all patients were taking at least 5 mg of prednisolone daily plus a bisphosphonate and appropriate calcium and vitamin D supplementation. Many already had osteoporotic T scores at this point. Fracture rates in our cohort are in line with published data, but substantially higher than those predicted from algorithms. Improvised algorithms using lumbar T scores were better at predicting risk than published methods. The only risk factor in our cohort that predicted subsequent fracture was lumbar spine T-score (Mean −1.2 versus −2.65 in the fracture group (P = 0.009)). Conclusions: Current algorithms underestimate risk, new charts should be created using lumbar T-scores. Our results emphasise that current prophylaxis strategies are not successful in preventing fractures in those who have osteoporosis and remain on prednisolone. Early osteoporosis prophylaxis and alternative treatments are essential to prevent fractures. References: Cohen A, Shane E, (2003). Osteoporosis after solid organ and bone marrow transplantation. Osteoporos Int 14, 617–30. Weinstein RS, (2011). Glucocorticoid-Induced Bone Disease. N Engl J Med 365, 62–70. World Health Organization Collaborating Centre for Metabolic Bone Diseases, University of Sheffield, UK. Online risk prediction tool. http://www.shef.ac.uk/FRAX/tool.jsp?country=1 (accessed 3 Nov 2011). Grossman JM, et al, (2010). American College of Rheumatology 2010 recommendations for the prevention and treatment of glucocorticoid-induced osteoporosis. Arthritis Care Res 62, 1515–26. No conflict of interest.